Pattern of Marginal Local Failure in a Phase II Trial of Neoadjuvant Chemotherapy and Stereotactic Body Radiation Therapy for Resectable and Borderline Resectable Pancreas Cancer. (March 2019) - Kharofa, Jordan; Mierzwa, Michelle; Olowokure, Olugbenga; Sussman, Jeffrey; Latif, Tahir; Gupta, Anumeha; Xie, Changchun; Patel, Sameer; Esslinger, Hope; Mcgill, Brian; Wolf, Eric; Ahmad, Syed A.
Abstract : Objectives: The main objectives of this study were to prospectively evaluate the safety and efficacy of stereotactic body radiation therapy (SBRT) in the neoadjuvant setting for resectable or borderline resectable pancreatic cancer. Materials and Methods: Eighteen patients were enrolled from November 2014 to June 2017. Following 3 cycles of chemotherapy, SBRT was delivered to the tumor and abutting vessel and a 3 mm planning target volume (PTV) margin to 33 Gy (6.6 Gy×5) with an optional elective PTV to 25 Gy (5 Gy×5) customized to the nodal space and mesenteric vessels. The primary endpoint is ≥grade 3 acute and late gastrointestinal toxicity. Results: Fifteen patients had borderline resectable tumors due to arterial abutment (n=7) or superior mesenteric vein encasement (n=8); 3 patients had resectable tumors. There were no ≥grade 3 acute or late gastrointestinal events. Following SBRT, surgery was performed in 12 patients (67%) with 11 (92%) R0 resections. The median overall survival and progression-free survival was 21 months (95% CI: 18-29) and 11 months (95% CI: 8.4-16). Progression occurred in 83% (10/12) of resected patients (distant [n=4, 40%], local-only [n=4, 40%], and local and distant [n=2, 20%]). The cumulative incidence of local failure (LF) at 12 months from resection was 50% (95% CI: 20-80). All LF were outside to the PTV33. Conclusions: Neoadjuvant SBRT was well tolerated, however LFs were predominantly observed outside the PTV33 volume that would have been covered with conventional RT volumes. The durability of local control after SBRT in the neoadjuvant setting merits examination relative to chemoradiation before incorporation into routine practice.